Stylized facts on bilateral trade and currency unions : implications for Africa - Tsangarides, Charalambos G.; Ewenczyk, Pierre; Hulej, Michal (IMF working paper ;, 2006)
This paper explores and quantifies several aspects of the performance of currency unions using an augmented version of the gravity model and focusing on two samples, the world and Africa. Our empirical findings suggest that, in principle, membership in a currency union should benefit Africa as much as it does the rest of the world. In addition, we find evidence from both samples that the effect of currency unions on trade is large, almost a doubling; currency unions are associated with trade creation, increase price co-movements among members, and make trade more stable; and longer duration of currency union membership brings about more benefits, although with some diminishing returns.